SARS-CoV-2 infections in patients with autoimmune blistering disorders: A case series and retrospective analysisCapsule Summary - Kimberly F. Breglio, MD, DPhil; Melissa M. Sarver, BS; Russell P. Hall, III, MD; Anne L. Marano, MD (Elsevier, 2022)
Background: Autoimmune blistering disorders (AIBDs) are rare, potentially life-threatening conditions often requiring immunosuppression. Throughout the SARS-CoV-2 pandemic, infection risk and mortality in patients with AIBDs are unknown. Objective: We report the outcomes of SARS-CoV-2 infections in patients with AIBDs and determined if patients on rituximab have an increased risk of SARS-CoV-2 infection. Methods: We examined clinical outcomes in 10 patients with AIBDs who developed SARS-CoV-2 infections at an American hospital. We performed a retrospective analysis of 132 patients with AIBDs enrolled in a clinical trial. Results: Patients with severe SARS-CoV-2 (n = 4) or death (n = 2) trended to be older. These patients had higher mortality than the national average (20% vs 1.6%). Our cohort included 52 patients with a history of rituximab treatment, 35 of whom were immunosuppressed by rituximab during the pandemic, and 45 patients never treated with rituximab. We found no difference between the rates of SARS-CoV-2 positivity in patients with AIBDs immunosuppressed by rituximab and those not on rituximab (9.1% vs 12.1%). Limitations: Testing for SARS-CoV-2 was performed on demand rather than surveillance. Overall transmission varied over time, and outcomes depended on accepted treatments. The small sample size of our cohort limits the generalizability of our results. Conclusion: This study suggests that rituximab does not increase the risk of SARS-CoV-2 test positivity in patients with AIBDs. However, these results should be interpreted with caution due to our relatively small sample size.